2020
DOI: 10.1371/journal.pone.0237228
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular non-compaction as a potential source for cryptogenic ischemic stroke in the young: A case-control study

Abstract: Background Up to 50% of ischemic strokes in the young after thorough diagnostic work-up remain cryptogenic or associated with low-risk sources of cardioembolism such as patent foramen ovale (PFO). We studied with cardiac magnetic resonance (CMR) imaging, whether left ventricular (LV) non-compaction-a possible source for embolic stroke due to sluggish blood flow in deep intertrabecular recesses-is associated with cryptogenic strokes in the young. Methods Searching for Explanations for Cryptogenic Stroke in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…LVNC cardiomyopathy is associated with a higher burden of arrhythmia, and prophylactic placement of automatic implantable cardioverter defibrillators may have a mortality benefit in selected cases [ 18 ]. Patients with LVNC are prone to left ventricular thrombus formation with increased risk of stroke [ 19 ]. However, the presence of LVNC alone is not sufficient for instituting prophylactic anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…LVNC cardiomyopathy is associated with a higher burden of arrhythmia, and prophylactic placement of automatic implantable cardioverter defibrillators may have a mortality benefit in selected cases [ 18 ]. Patients with LVNC are prone to left ventricular thrombus formation with increased risk of stroke [ 19 ]. However, the presence of LVNC alone is not sufficient for instituting prophylactic anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…All subjects were imaged with a 1.5-T Avanto fit magnetic resonance scanner (Siemens Healthcare, Erlangen, Germany) using a 32-channel receiver body coil and ECG-gating, as described previously. 15 Specific technical parameters for each sequence type are given in ( online supplemental table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…26,28 A proposed strategy for anticoagulation therapy in noncompaction cardiomyopathy A recent case-control study in young adults (age 18-49) presenting with an imaging-positive ischaemic stroke of undetermined aetiology showed that the percentage of non-compacted LV volume was higher in patients with cryptogenic stroke compared with stroke-free controls of similar age and gender. 51 Importantly, a 5% increase in non-compacted ventricular volume at cardiac MRI has been associated with a nine-fold increased risk of cryptogenic ischaemic stroke. 51 Furthermore, several case reports seem to confirm the close relationship between NCCM and juvenile stroke.…”
Section: Noncompaction Cardiomyopathy Per Sementioning
confidence: 99%